INDONESIA’S STRATEGY AND DIPLOMACY IN THE SOUTH CHINA SEA CONFLICT - Ahmad Zainal Mustofa (The Republic of Indonesia Defense University, 2022)
This study describes the government's strategy in Indonesia under the leadership of Joko Widodo to strengthen the Natuna border area. The Natuna area is a point of discussion as there are often territorial conflicts. This study aims to answer the question about the government's strategy to strengthen the border zone in Natuna. This study uses library research methodology and the Revolution in Military Affairs (RMA) concept to analyze the process. After conducting research, it can be concluded that to reinforce the border area at Natuna, the government is making efforts to improve the military posture by constructing several new military units. Then the government is also looking at diplomatic means in the ASEAN region to resolve the territorial dispute with China in the South China Sea. This is because there is no mutual agreement, considering that Indonesia is based on the 1982 UNCLOS, while China has a view of the Nine-Dash Line.Â